Meta-Analysis of Students' Cognitive Abilities and Critical Thinking Skills Through the STEM Integrated Learning Model - Daulay, Hermalina; Asrizal; Usmeldi; Syefrinando, Boby (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2023)
The purpose of this study was to see how the STEM integrated learning model influences the cognitive abilities and critical thinking skills of students in physics subjects. This type of research is meta-analysis research. The sample used was 18 articles that met the criteria. There are two dependent variables used in this study, namely cognitive abilities and critical thinking skills. While the moderator variable is based on classes, lessons and learning models. The data collection technique used is through coding, with data analysis techniques using effect size techniques. Based on the data that has been analyzed in this study, it can be concluded that: 1) The STEM integrated learning model is proven to have an impact on student's cognitive abilities, especially if the learning model is integrated with the PBL learning model, and can have an influence on students' critical thinking skills, especially if integrated with the PJBL learning model, 2) The STEM integrated learning model is proven to have an impact on students' cognitive abilities, especially in class XII, and can have an influence on students' critical thinking skills, especially in class IX, 3) The STEM integrated learning model is proven to have an impact on students' cognitive abilities, especially on thermodynamic material, and can have an influence on students' critical thinking skills, especially on dynamic electricity material.